Sustainability Design Principles for a Wildlife Management Analytics System: An Action Design Research. Issue 4 (4th July 2021) - Pan, Shan L.; Li, Mingwei; Pee, L.G.; Sandeep, M.S.
ABSTRACT: Wildlife management is becoming increasingly critical to improving the sustainability of biodiversity and the welfare of human beings. This paper uses affordance as a lens to explore the design of information systems that can assist in managing wildlife in protected areas. Through an action design research (ADR) study with a forest department, we develop and test design principles for a class of wildlife management analytics system (WMAS). We identify the initial design principles, including elements of the action potential, materiality, and boundary condition, and iteratively refine them based on an instantiation of WMAS through two iterations of design and implementation cycles. Through our work, we contribute to design knowledge by abstracting the artefacts, design principles in particular, and the ADR approach by generalising two new activities and corresponding principles when designing analytical models. Our findings can also be used to address a class of similar problems and systems in practice.